Optimization of Media Product Utilization Geography Learning for Teachers of SMPN 3 Painan - Tanamir, Momon Dt; Setriani, Loli; Rianto, Slamet (PT FORMOSA CENDEKIA GLOBAL, 2024)
Teachers in the current era of technology 5.0 must be able to carry out learning by utilizing IT in compiling learning media. Teachers still need to improve their competence, especially in developing IT-based learning media in learning activities by improving their skills through training activities. One of the efforts that can be carried out is by distributing research products for developing student learning media such as Assembler Edu, Thunkable, Chamilo, Kudloar, and Lectora Inspire. Likewise with research products developed by University Geography Education Study Program students PGRI West Sumatra which can be optimized by teachers in schools in designing learning media. the existence of these learning media can increase motivation and students' understanding in absorbing information in learning activities, so that learning objectives and learning outcomes are still achieved.